Amendment Of Company Law: Resolving Demission State Of directors and Board of Commissioners Issue - Suhardiman, Daniel; Pramono, Nindyo (Advances in Social Sciences Research Journal, 2023)
Law No. 40 of 2007 concerning Limited Liability Companies ("Law No. 40/2007") has become the main regulation with regard to corporate law for 15 consecutive years. During the enactment of Law No. 40/2007, there are several unsolvable issues that requires an amendment to the company law. One of the issues relate to Directors and Board of Commissioners term of office. In practice, the term of office for the Board of Directors and Board of Commissioners varies according to the articles of association of each company. Obstacles that may occur in the practice of running a company are obstacles in reappointing or replacing Directors and Commissioners whose term of office has ended. This is due to the absence of preventive arrangements in terms of the reappointment or replacement of the Directors and the Board of Commissioners whose term of office has ended due to a deadlock in holding the General Meeting of Shareholders ("GMS"). The Directors and Board of Commissioners will be in a state of demission and will no longer be able to act for and on behalf of the Company. Law No. 40/2007 has yet regulated such matters and leave the issues unsolvable. This study aims to discuss and analyze the amendment of Law No. 40/2007 to overcome the demission state of Directors and Board of Commissioners.